Indigenous Cellulosic Raw Materials for the Production of Pulp, Paper and Board - Bhat, R. V.; Virmani, K. C. (Indian Forester, 1954)
In India, bagasse (crushed sugarcane) is produced to the extent of over 1.5 million tons (on the bone-dry basis) in sugar mills. It is mostly used for burning in boilers for raising steam in the sugar mills themselves. This cellulosic material is used to some extent for the production of various kinds of papers in some parts of the world growing sugarcane. Intensive research work carried out in foreign countries prior to 1938 led to the conclusion that it is essential to remove pith from bagasse if this fibrous material is to be used for the manufacture of good quality writing and printing papers. Processes used in foreign countries for the manufacture of pulp from bagasse require special patented machinery and licence of the inventors for their use by others. With a view to developing a process suitable to Indian conditions, an investigation was undertaken at this Institute on the separation of pith from bagasse and making writing and printing papers from the depithed material. Laboratory and pilot plant experiments gave encouraging results. A successful commercial run was carried out in Shree Gopal Paper Mills Ltd., Jamuna Nagar (Punjab), using 70% of bagasse pulp and 30% of bamboo pulp. This paper was used for printing a dak edition of The Statesman, New Delhi. Papers were also made on the pilot plant from mixtures of bagasse pulp with sabai grass and ulla grass (Themeda arundinacea) pulps and by adding bagasse pith to the bagasse pulp. Samples of all these papers are appended in this bulletin. A sheet of the The Statesman printed on the bagasse-bamboo paper is also appended.